Emerging Immigration Scholars Conference: University of California Los Angeles, USA, February 26th–27th 2016 - Jirka, Luděk (Lidé města, 2016)
On February 26th and 27th a conference took place at the University of California in Los Angeles, organized by the University of California Los Angeles Center for the Study of International Migration. While the conference mainly concerned migration, multiculturalism and immigration into the United States, there were also other interesting topics. Many participants were post-doctoral fellows, fresh holders of doctorate degrees, who had finished their fieldwork as well as their dissertation thesis and wanted to publish their thesis. Each session was led by “older local” professors from the University of California Los Angeles, San Diego, Irvine and Berkeley, while the presenters were from all over the United States. There were no presenters from any other countries.